Reduced caveolae density in arteries of SHR contributes to endothelial dysfunction and ROS production - Potje, Simone R.; Grando, Marcella D.; Chignalia, Andreia Z.; Antoniali, Cristina [UNESP]; Bendhack, Lusiane M. (Nature Publishing Group, 2019)
Caveolae are plasma membrane invaginations enriched with high cholesterol and sphingolipid content; they also contain caveolin proteins in their structure. Endothelial nitric oxide synthase (eNOS), an enzyme that synthesizes nitric oxide (NO) by converting L-arginine to L-citrulline, is highly concentrated in plasma membrane caveolae. Hypertension is associated with decreased NO production and impaired endothelium-dependent relaxation. Understanding the molecular mechanisms that follow hypertension is important. For this study, we hypothesized that spontaneously hypertensive rat (SHR) vessels should have a smaller number of caveolae, and that the caveolae structure should be disrupted in these vessels. This should impair the eNOS function and diminish NO bioavailability. Therefore, we aimed to investigate caveolae integrity and density in SHR aortas and mesenteric arteries and the role played by caveolae in endothelium-dependent relaxation. We have been able to show the presence of caveolae-like structures in SHR aortas and mesenteric arteries. Increased phenylephrine-induced contractile response after treatment with dextrin was related to lower NO release. In addition, impaired acetylcholine-induced endothelium-dependent relaxation could be related to decreased caveolae density in SHR vessels. The most important finding of this study was that cholesterol depletion with dextrin induced eNOS phosphorylation at Serine(1177) (Ser(1177)) and boosted reactive oxygen species (ROS) production in normotensive rat and SHR vessels, which suggested eNOS uncoupling. Dextrin plus L-NAME or BH4 decreased ROS production in aorta and mesenteric arteries supernatant's of both SHR and normotensive groups. Human umbilical vein endothelial cells (HUVECs) treated with dextrin confirmed eNOS uncoupling, as verified by the reduced eNOS dimer/monomer ratio. BH4, L-arginine, or BH4 plus L-arginine inhibited eNOS monomerization. All these results showed that caveolae structure and integrity are essential for endothelium-dependent relaxation. Additionally, a smaller number of caveolae is associated with hypertension. Finally, caveolae disruption promotes eNOS uncoupling in normotensive and hypertensive rat vessels and in HUVECs.